Constitutive Equations for Microstructural Features Developed During Solid Particle Erosion of 52100 Steel - Mukhopadhyay, Prantik (Defence Science Journal, 2020)
Solid particle erosion of the 52100 bearing steel induced the normal growth of the tempered lath martensite, the low angle boundaries and the recovery islets. Microstructural features were revealed using the electron microscopy. Constitutive equations for the normal growth of the tempered lath martensite, energies of the low angle boundaries, and size of the recovery islets have been derived. The normal growth rate of the tempered lath martensite has been derived from the oriented mobility of the boundary in crystallite-stress fields, the driving force from the boundary energy and the pinning force from the uniformly distributed precipitates. Read-Shockley equation has been redefined using the dislocation density term as the misorientation of the boundary. An advanced Read-Shockley equation has been used for predicting the size of the recovery islets (0.12 mm to 0.27 mm) from the local energy equilibrium of the recovered tempered lath martensite, and validated by the TEM bright field microscopic study.